2011
DOI: 10.1039/c0em00659a
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the contributions of long range transported aerosol in East Asia to carbonaceous aerosol and PM concentrations in Seoul, Korea using highly time resolved measurements: a PSCF model approach

Abstract: The contributions of long range transported aerosol in East Asia to carbonaceous aerosol and particulate matter (PM) concentrations in Seoul, Korea were estimated with potential source contribution function (PSCF) calculations. Carbonaceous aerosol (organic carbon (OC) and elemental carbon (EC)), PM(2.5), and PM(10) concentrations were measured from April 2007 to March 2008 in Seoul, Korea. The PSCF and concentration weighted trajectory (CWT) receptor models were used to identify the spatial source distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 38 publications
1
53
0
1
Order By: Relevance
“…Thus, to avoid uncertainties that can occur due to a limited amount of available data, an arbitrary weight function W(n ij ) as shown in Eq. (2) is multiplied with the PSCF value (Jeong et al, 2011).…”
Section: Potential Source Contribution Functionmentioning
confidence: 99%
“…Thus, to avoid uncertainties that can occur due to a limited amount of available data, an arbitrary weight function W(n ij ) as shown in Eq. (2) is multiplied with the PSCF value (Jeong et al, 2011).…”
Section: Potential Source Contribution Functionmentioning
confidence: 99%
“…Model comparisons found comparable results when Concentration Fields (using logarithmic concentrations), CWT, and PSCF were applied to virtual sources and modeled concentrations (Kabashnikov et al, 2011). When applied to field carbonaceous aerosols and PM measurements, good agreement was attained between PSCF and CWT models (Jeong et al, 2011). Han et al (2007) conducted comparisons between PSCF and RTWC and found there were some differences in the source areas identified for total gaseous mercury concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…unlikely for airflow to pass over a particular area). Known as the tailing effect, the few number of trajectory segment endpoints can lead to the false identification of source areas because the concentrations are uniformly weighted along a trajectory (Watson et al, 2008;Jeong et al, 2011). Although a minimum of 2 trajectory segment endpoints per grid cell seems like a small number, it is equivalent to two sets of 3 h Hg concentrations and trajectory residence times in the seasonal CWT calculation.…”
Section: Determination Of Concentration-weighted Trajectory (Cwt)mentioning
confidence: 99%
See 2 more Smart Citations